Socio-Economic Status of Household in Meerut Slum Area: Exploring the socio-economic and health states of youngster workers in slum areas of Meerut, India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This review is an endeavor to explore the socio-economic and health states of youngster workers in chose slum areas of Meerut city, India. The slums have turned into a certain piece of the Indian metropolitan scene and have been made because of the pull of economic security and social respect. Slums in the city are portrayed by an absence of fundamental conveniences and facilities. The youngster workers from these slum areas are occupied with sloppy, casual, and unregulated areas of the economy and are not being accounted for in true measurements. The review is basically founded on the essential information identified with different determinants and natural parts of the inspected youngster workers from 6 slums in Meerut city. The outcomes show that the youngsters are compelled to work in the work market at an early age because of the hopeless economic states of the guardians and lack of education. Youngster laborers in the slum areas are at steady danger of health perils due to helpless living and unhygienic workplaces in the review area.